Social context and prey composition are associated with calling behaviour in a diving seabird. (6th January 2020) - McInnes, Alistair M.; Thiebault, Andrea; Cloete, Trevor; Pichegru, Lorien; Aubin, Thierry; McGeorge, Cuan; Pistorius, Pierre A.
Abstract : Social cohesion and prey location in seabirds are largely enabled through visual and olfactory signals, but these behavioural aspects could potentially also be enhanced through acoustic transfer of information. Should this be the case, calling behaviour could be influenced by different social–ecological stimuli. African Penguins Spheniscus demersus were equipped with animal‐borne video recorders to determine whether the frequency and types of calls emitted at sea were dependent on behavioural modes (commuting, sedentary and dive bout) and social status (solitary vs. group). For foraging dive bouts we assessed whether the timing and frequency of calls were significantly different in the presence of schooling prey vs. single fish. The probability of call events was significantly more likely for birds commuting early and late in the day (for solitary birds) and during dive bouts (for groups). During foraging dive bouts the frequency of calls was significantly greater for birds diving in the presence of schooling fish and birds called sooner after a catch in these foraging scenarios compared with when only single fish were encountered. Three call types were recorded, 'flat', 'modulated' and 'two‐voice' calls, but there was no significant relationship detected with these call types and behavioural modes for solitary birds and birds in groups. The results of this study show that acoustic signalling by African Penguins at sea is used in a variety of behavioural contexts and that increased calling activity in the presence of more profitable prey could be of crucial importance to seabirds that benefit from group foraging.